Paratricepital approach for open reduction and internal fixation of delayed presentation of pediatric supracondylar humerus fracture - Subbasetty, Ramachandra; Manjunath, Dayanand; Shivanna, Deepak; Murthy, Narasimha (International Journal of Research in Orthopaedics, 2019)
Background: Delayed presentation of pediatric displaced supracondylar humerus fracture is relatively common. Management of such cases have higher incidence of perioperative complications and usually require open reduction and pinning. Open reduction can be done by various approaches, each having its own advantage and disadvantages. Methods: A prospective study was done comprising 20 children with displaced Supracondylar fracture presented 2-14 days of injury, Mean patient age was 6 years. 15 were boys and 5 were girls. Children in whom closed reduction and percutaneous pinning was achieved, vascular injury and more than 2 weeks old fracture cases were excluded. Paratricepital approach was used for Open reduction and pinning for all the cases. The functional outcome was assessed using Flynn criteria. Results: In all cases the fracture had united at complete follow-up and the mean follow-up period was 16 months. The outcome was excellent in 15 (75%), good in 3 (15%), fair in 1 (5%), and poor in 1 (5%) patients. The mean Baumann angle was 76º in the affected elbow and 73º in the normal elbow. Average time for complete union in the current study was 7 weeks. Pin tract infection was seen in 2, stiffness in 2 patients, cubitus varus in 1 patient. No case of compartment syndrome or iatrogenic nerve injury was seen was recorded. Conclusions: Finally, we concluded that triceps sparing paratricepital approach is an easy, simple and safe approach for exposure and internal fixation of supracondylar humeral fractures in children with excellent functional outcome.